2017
DOI: 10.1016/j.socscimed.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Water insecurity in a syndemic context: Understanding the psycho-emotional stress of water insecurity in Lesotho, Africa

Abstract: Syndemics occur when populations experience synergistic and multiplicative effects of co-occurring epidemics. Proponents of syndemic theory highlight the importance of understanding the social context in which diseases spread and cogently argue that there are biocultural effects of external stresses such as food insecurity and water insecurity. Thus, a holistic understanding of disease or social vulnerability must incorporate an examination of the emotional and social effects of these phenomena. This paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 31 publications
5
91
0
Order By: Relevance
“…This finding also affirms the fact that water insecurity is inextricably linked with food insecurity and has significant implications for sustainable development and poverty reduction [97,98]. The positive correlation between water insecurity and maternal stress also points to the psychosocial effects that water insecurity could have on households [4,20,99]. Future research will benefit from exploring the joint influences of food and water insecurity on health and well-being.…”
Section: Discussionsupporting
confidence: 69%
“…This finding also affirms the fact that water insecurity is inextricably linked with food insecurity and has significant implications for sustainable development and poverty reduction [97,98]. The positive correlation between water insecurity and maternal stress also points to the psychosocial effects that water insecurity could have on households [4,20,99]. Future research will benefit from exploring the joint influences of food and water insecurity on health and well-being.…”
Section: Discussionsupporting
confidence: 69%
“…Psychosocial stress and anxiety have increasingly been appreciated as important individual‐level components of water insecurity that shaped water seeking behavior (Collins et al, 2018; Hadley & Wutich, 2009; Mushavi et al, 2020; Workman & Ureksoy, 2017). Both a lack of water access and the process of negotiating access could lead to psychosocial distress, and women have borne most of this burden given the gender inequities in household water management responsibilities in many societies (Bisung & Elliott, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, some of this newer work has shown that water insecurity is associated with symptoms of common mental disorders, as measured by validated screeners for symptoms of common mental disorders such as anxiety and depression (Aihara et al, ; Cooper‐Vince et al, ; Stevenson et al, ; Subbaraman et al, ; Workman & Ureksoy, ). In our own work in Bolivia, we found in a study of women from 28 informal communities that water insecurity was not just associated with emotional distress; it was also associated with symptoms of common mental disorders like anxiety and depression as measured by the Standard Reporting Questionnaire and Hopkins Symptom Checklist (Wutich, Brewis, et al, ).…”
Section: Recent Research On Water Insecurity and Distressmentioning
confidence: 99%
“…Farhana Sultana (), based on her work in Bangladesh, Ennis‐McMillan's (, ) work in Mexico, my work in Bolivia (Wutich & Ragsdale, ), and my cross‐cultural work with Alex Brewis (Wutich & Brewis, ) all indicate that stigma, uncertainty, and social injustice are key mechanisms for understanding when and why water insecurity causes negative psychosocial outcomes. Beyond this, Tallman () on biocultural vulnerabilities in Bolivia and Workman and Ureksoy () on syndemics in Lesotho indicate that these dynamics can be incredibly complex.…”
Section: Future Directionsmentioning
confidence: 99%